The relationship between cultural orientation and reward preference: a study conducted in South Africa and the Netherlands - Van Eijk, Jeff (Organisational Psychology, 2017)
Orientation: Organisations operating in multiple countries and continents, referred to as multinationals, often experience cultural barriers when interacting with employees from the host county. These barriers, in turn, frequently result in counterproductive outcomes for the organisation. Being able to adapt Human Resource (HR) policies and practices to the cultural values and norms of the host country, multinationals will be better able to attract, motivate and retain their host country employees and achieve the strategic objectives they have set. Research purpose: The aim of the current study was to investigate the relationship between an individual's reward preference and his/her cultural orientation by means of a novel methodological approach, while further investigating this relationship in two culturally distinct countries to allow for a comparison to be made. Motivation for the study: Research linking rewards to cultural orientation is characterised by mixed findings, which could be related to cross-cultural measurement issues (for example, issues of level of analysis and the reference-group effect). By measuring at an individual level of analysis and exploring the use of choice-based conjoint analysis, the present study aimed to advance the field of cross-cultural remuneration research. The study aimed to show that, by linking cultural orientation and reward preference, multinationals can be helped to optimize their remuneration policies and practices in a way that brings about desired organisational outcomes. Research design: A descriptive research design using quantitative methods was employed. Data was collected from employees in both South Africa (n = 132) and the Netherlands (n = 152). Survey items, responded to on a Likert-type response scale were used to measure an individual's reward preference and cultural orientation. To explore the potential bias introduced by the reference-group effect in cross-cultural reward research, a choice-based conjoint analysis was included to measure reward preference. Data from the field survey was analysed using descriptive and inferential statistics. Choice-based conjoint analysis was used to determine the relative importance of each reward element. Main findings: The results of the Multiple Regression analysis revealed that certain cultural orientations were significantly positively related to reward preference. These included the relationship between collectivism and group bonuses; uncertainty avoidance and job security; uncertainty avoidance and base pay; and long-term orientation and future oriented rewards. Uncertainty avoidance and long-term orientation were positively related to financiallyoriented reward elements. The conjoint analysis allowed for further differentiation between these elements. Practical implications: Multinationals will be able to better align their reward policies and practices with the preferences of employees who come from different cultures and who therefore possess differing cultural orientations. By doing so, multinationals will be able to improve their capability to attract, motivate and retain employees that come from distinct cultural backgrounds. Research contributions: By taking a different methodological approach using choice-based conjoint analysis, this study showed that the preference for particular reward packages can not be solely reduced to linear relationships. In contrast to previous studies, this study was able to incorporate a single sample for both the dependent and the independent variables by measuring the cultural orientations at an individual level of analysis.